The structure of bacterial communities of some species of the genus Solidago L. - T. Dobrovol’skaya; T. Khusnetdinova; P. Savitskaya; O. Shelepova (Социально-экологические технологии, 2019)
The abundance and taxonomic structure of the epiphytic bacterial communities of three species of the genus Solidago (Solidago virgaurea L., Solidago canadensis L., Solidago gigantea Aiton) from natural habitats was determined. It was established that in goldenrod during vegetation period, the number of bacteria of the epiphytic complex on leaves and roots increases by 1–2 orders of magnitude, in the soil under the studied plants, the density and taxonomic structure of the bacterial complex did not change much. In all the periods of sampling on the leaves of 3 species of goldenrod, among the epiphytic bacteria of the phyllosphere, pigmented forms of proteobacteria dominated, no replacement of eccisotrophic proteobacteria with bacteria of the hydrolytic complex was recorded. In inflorescences and seeds in Solidago canadensis and Solidago gigantea, the pigmented forms of proteobacteria were also dominant, their share was 60–100%, while in inflorescences of S. virgaurea they were in minor quantities, and apigmented forms of proteobacteria dominated.